2007
DOI: 10.1128/iai.00120-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification of theActinobacillus pleuropneumoniaeLeucine-Responsive Regulatory Protein and Its Involvement in the Regulation of In Vivo-Induced Genes

Abstract: Actinobacillus pleuropneumoniae is a gram-negative bacterial pathogen that causes a severe hemorrhagic pneumonia in swine. We have previously shown that the limitation of branched-chain amino acids (BCAAs) is a cue that induces the expression of a subset of A. pleuropneumoniae genes identified as specifically induced during infection of the natural host animal by using an in vivo expression technology screen. Leucineresponsive regulatory protein (Lrp) is a global regulator and has been shown in Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…We have previously shown that A. pleuropneumoniae ilvI, which is required for BCAA biosynthesis, is upregulated both in vivo during infection (22) and in CDM lacking BCAA (CDMϪBCAA) compared to complete CDM (CDMϩBCAA) (55) and that leucine-responsive regulatory protein, encoded by the gene lrp, is required for the response of ilvI to BCAA limitation (54). To determine whether expression of ilvI and lrp correlates with the concentrations of BCAA available in the porcine lung, we used luciferase reporter assays and quantitative RT-PCR to measure the expression of these genes in CDM samples containing various concentrations of BCAA.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that A. pleuropneumoniae ilvI, which is required for BCAA biosynthesis, is upregulated both in vivo during infection (22) and in CDM lacking BCAA (CDMϪBCAA) compared to complete CDM (CDMϩBCAA) (55) and that leucine-responsive regulatory protein, encoded by the gene lrp, is required for the response of ilvI to BCAA limitation (54). To determine whether expression of ilvI and lrp correlates with the concentrations of BCAA available in the porcine lung, we used luciferase reporter assays and quantitative RT-PCR to measure the expression of these genes in CDM samples containing various concentrations of BCAA.…”
Section: Resultsmentioning
confidence: 99%
“…Luciferase reporter assays. Expression from the ilvI promoter was quantified by using a luciferase expression plasmid (pIviI) in which the ilvI promoter drives the expression of promoterless luxAB genes (54). Wild-type A. pleuropneumoniae strain AP225 containing pIviI grown overnight on BHI agar supplemented with 10 g of V factor/ml (BHIV) containing 50 g of ampicillin/ml was suspended in CDMϪBCAA and then diluted to an optical density at 520 nm (OD 520 ) of ϳ0.2 in 30 ml of prewarmed CDM containing 50 g of ampicillin/ml and supplemented with 0, 10, 20, 50, or 100% of the concentration of BCAA found in complete CDM.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations